Evaluation of Thrombolytic, Membrane Stabilizing, Antidiarrhoeal and Analgesic Activities of Leaves of Triumfetta pilosa - Ahmed, Tanvir; Bala, Amiyo; Uddin, Jalal; Labu, Zubair Khalid (Bangladesh Pharmaceutical Journal, 2016)
The aim of the research has been focused on the phytochemical investigation of the plants which have ethno-botanical and folkloric importance for drug discovery. The widespread availability and folkloric use of Triumfetta pilosa leaves led us to determine the pharmacological potential of the plant through in vitro and in vivo experiments. The crude ethanolic extract (EE) of T. pilosa leaves were partitioned successively using solvent of different polarities. Then these fractions were subjected to qualitative and quantitative phytochemical screening by standard procedures. The extract of T. pilosa and its fractions were evaluated for their possible thrombolytic, membrane stabilizing, antidiarrhoeal and analgesic activities by using standard drugs streptokinase, acetyl salicylic acid, loperamide and diclofenac-Na, respectively. In the study for thrombolytic activity, among all partitionates, the ethyl acetate soluble fraction (ESF) showed the highest percent of clot lysis (58.67%) as compared to standard streptokinase (69.23%) and water (3.77%). Also, in case of membrane stabilizing activity, ESF significantly inhibited the haemolysis of human erythrocyte membrane both induced by hypotonic solution (65.33 ± 0.50%) and heat (56.22 ± 0.69%), as compared to standard acetyl salicylic acid (ASA) (71.12 ± 26%) and (75.92 ± 0.29%), respectively. In the antidiarrheal assay, the crude ethanolic extract inhibited the mean number of defecation by 45.71% and 63.18% at 200 and 400-mg/kg body weight, respectively. During assay for central and peripheral analgesic activity at dose of 400-mg/kg, the extract showed reaction times of 5.11 (p < 0.001) and 1.96 (p < 0.001) min in the tail-flick and tail-immersion models, while the normal and reference groups exhibited reaction times of 11.66, 1.46; (p < 0.001) and 4.91, 1.16; (p < 0.001) in the tail flick and tail immersion method, respectively. At 400 mg/kg, the extract showed 49.22% inhibition of acetic acid induced writhing in mice model. Bangladesh Pharmaceutical Journal 19(2): 226-232, 2016